Strangulated small-bowel loop herniation at the 5 mm trocar entry site after laparoscopic ovarian cyst excision operation - Dilek Yüce; Süleyman Salman; Serkan Kumbasar; Güray Tuna (Barpeta Obstetrics and Gynaecological Society, 2020)
To draw attention to the clinical approach in terms of early diagnosis in the trocar entry site hernias which are rare complications after laparoscopic operations. A 47 years old female patient was admitted to our clinic with complaint of ongoing pelvic pain and the patient was scheduled for laparoscopic cystectomy. On the 13th day postoperatively, the patient was referred to our clinic again with ileus clinic. In the CT scan, incarcerated intestinal herniation was detected at the 5 mm trocar entry site. As the trocar site hernias can occur even in incisions smaller than 10 mm,early diagnosis and treatment is of vital importance.